Inovasi Pembelajaran Pendidikan Islam pada Pendidikan Dasar - Alirahman, Agus Dian (Permata : Jurnal Pendidikan Agama Islam, 2021)
Islamic Religious Education can be defined as education carried out based on Islamic teachings. But nowadays Islamic Religious Education as a scientific discipline and subjects at every level of education still finds obstacles, including that it has not received the attention of students, this is because it is better known as a subject whose material content is dominated by memorization and does not pay attention to the development of learning strategy designs. Concrete efforts are needed to improve learning in Islamic Education subjects, especially at the basic education level. As a solution, it is necessary to make innovations in Islamic education learning, namely innovations that are able to improve learning through problematic studies and strategic solutions for the implementation of Islamic education through a constructive model. The implementation of Islamic Education learning in schools is not only oriented towards rote learning, it is not only inclined to teacher centered. The constructivism learning model seems to be one of the answers that provides knowledge and shapes the attitudes, personalities, and skills of students in practicing teachings. The constructive learning model is able to have an impact on the activity of students or students are preferred. The teaching and learning process in the constructivism model is characterized more by student centered than teacher centered. Constructive model innovation is able to become a strategic solution in improving the implementation of Islamic Education learning at the basic education level. Abstrak Pendidikan Agama Islam dapat diartikan sebagai pendidikan yang dilaksanakan berdasarkan ajaran Islam. Namun dewasa ini Pendidikan Agama Islam sebagai disiplin keilmuan dan mata pelajaran di setiap jenjang pendidikan masih menemukan kendala, diantaranya belum mendapat perhatian para siswa, hal itu dikarenakan lebih dikenal sebagai mata pelajaran yang muatan materinya didominasi pada hafalan serta kurang memperhatikan perkembangan disain strategi pembelajaran. Perlu usaha konkret untuk meningkatkan pembelajaran mata pelajaran Pendidikan Islam khususnya pada jenjang Pendidikan Dasar. Sebagai sebuah solusi maka perlu melakukan inovasi dalam pembelajaran Pendidikan Islam, yakni inovasi yang mampu meningkatkan pembelajaran melalui kajian problematika dan solusi strategis penyelenggaraan pendidikan Islam melalui model konstruktif. Penyelenggaraan pembelajaran Pendidikan Islam di sekolah tidak hanya berorientasi pada hafalan-hafalan saja, tidak hanya condong kepada teacher centered. Model pembelajaran konstruktivisme nampaknya merupakan salah satu jawaban yang memberikan pengetahuan dan membentuk sikap, kepribadian, dan keterampilan peserta didik dalam mengamalkan ajaran. Model pembelajaran konstruktif mampu memberikan dampak keaktivan siswa atau peserta didik lebih diutamakan. Proses belajar mengajar pada model konstruktivisme lebih diwarnai student centered daripada teacher centered. Inovasi model konstruktif mampu menjadi solusi strategis dalam peningkatan penyelengaraan pembelajaran Pendidikan Islam pada jenjang Pendidikan Dasar